Effective catalysts for hydrogenation of CO2 into lower olefins: A review - Okoye-Chine C.G.; Mbuya C.O.L.; Shiba N.C.; Otun K.O. (Elsevier Ltd, 2025)
Utilizing CO2 as a carbon source to produce high-value compounds, such as light olefins, is one of the most promising approaches to mitigate CO2 emissions. Efficient catalysts are critical for optimizing selectivity and yield of light olefins, which is necessary to make the CO2-to-light olefin process economically viable. Therefore, this review focused on various Fe-based catalysts and multifunctional catalysts containing zeolite used for producing short-chain olefins via CO2 hydrogenation. There are currently two main strategies to hydrogenate CO2 into light olefins in a single step: the CO2?FTS route and the MeOH-mediated route. The primary objective of the CO2-FT approach is to selectively produce the necessary C2?C4 olefins, with a focus on the coordination of active metals, promoters, and supports to adjust the surface H/C ratio, which is crucial for the formation of C2?C4 olefins. However, obtaining a high productivity of C2?C4 olefins from CO2 hydrogenation requires a significant improvement in activity with inhibiting secondary reactions. Currently, tandem catalysts containing SAPO-34 are currently favoured for the higher production of short-chain olefins from the hydrogenation of CO2, owing to their high oxygen vacancies, zeolite topology, and zeolite acidity. Specifically, In2O3-based formulations are sufficiently promising to get past the drawbacks of traditional iron catalysts. Tandem catalysts with metal oxide In2O3/ZrO2 and SAPO-34 components demonstrated promising results in reducing CO product poisoning. This article describes the latest progress, challenges, and prospects for research concerning CO2 hydrogenation into short-chain olefins using iron-based catalysts and alternative catalysts with multifunctional properties. ? 2024 The Author(s)